TPU air-tight membrane, its preparation method and application in inflatable floating bridge
By modifying bentonite through cationic intercalation and blending it with polyurethane, a TPU air-tight membrane was prepared, which solved the problem of insufficient air tightness of polyurethane membrane materials, achieved efficient gas barrier and improved mechanical properties, and is suitable for the inner sealing air membrane of inflatable floating bridges.
Patent Information
- Application Number
- CN202610013152.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-07
- Publication Date
- 2026-03-20
- Estimated Expiration
- 2046-01-07
AI Technical Summary
Polyurethane membrane materials have high air permeability but poor air tightness, which limits their application in sealed air membranes, packaging films, and other applications.
Modified bentonite was prepared by cationic intercalation modification and then melt-blended with polyurethane to form a TPU air-tight membrane. The strong hydrogen bonding effect formed by the urethane groups improved the interfacial bonding force and compatibility between bentonite and polyurethane, forming a continuous barrier network.
It improves the barrier and mechanical properties of TPU air-tight membranes, reduces gas permeability, and enhances their application effect in inflatable floating bridges.
Smart Images

Figure CN121450086B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of polyurethane, in particular to a TPU closed air film, a preparation method thereof and application thereof in inflatable floating bridge. BACKGROUND
[0002] Polyurethane has rigidity of plastic and elasticity of rubber, and has good shock buffering, wear resistance, heat resistance and other properties, and can be made into films, coatings, boards and the like, and is widely used in medical devices, automobile manufacturing, transportation and other aspects. However, the air permeability of polyurethane film material is relatively large, and the air tightness is poor, which limits the practical application of polyurethane film in closed air film, packaging film and the like.
[0003] Bentonite is rich in source, cheap and easy to obtain, and has good mechanical properties, and has important application in plastic, rubber and other materials. Patent with publication number CN117603558B discloses a polyurethane composition for display screen packaging and a preparation method thereof, which takes polyurethane, polyester resin, sheet bentonite modified whisker agent and the like as raw materials, and the prepared polyurethane composition has good water vapor barrier property, cold and hot impact resistance and other properties, but bentonite is easy to aggregate, and has poor dispersibility in polyurethane, which will affect the mechanical properties and the like of polyurethane, so it is necessary to organically modify bentonite. SUMMARY
[0004] (I) The technical problem solved: In view of the deficiencies of the prior art, the present application provides a TPU closed air film, which solves the problem of poor barrier property of polyurethane film material, and has good mechanical properties at the same time.
[0005] (II) Technical scheme: A preparation method of a TPU closed air film:
[0006] (1) Add bis(2-hydroxyethyl)acetamide bromide, alkyl isocyanate and dibutyl tin dilaurate into dichloromethane, filter after reaction, rotary evaporate the filtrate, recrystallize the product in ethanol to obtain an intercalation agent intermediate.
[0007] (2) Add the intercalation agent intermediate and an aqueous solution of trimethylamine into ethanol, filter after reaction, volatilize the filtrate by heating, cool in an ice water bath, recrystallize the product to obtain a cationic intercalation agent, and the preparation reaction formula is as follows:
[0008] .
[0009] (3) Add bentonite into water, ultrasonic dispersion, add the cationic intercalation agent and ethanol, modify by stirring, wash the filter cake with ethanol after filtration, and dry to obtain modified bentonite.
[0010] (4) Mix polyurethane and modified bentonite, melt extrude through a screw extruder, then blow the granules into a film through a film blowing machine to obtain a TPU closed air film.
[0011] Preferably, the amount of bis(2-hydroxyethyl)acetamido bromide in (1) is 100 parts by weight, the amount of alkyl isocyanate is 66-140 parts by weight, and the amount of dibutyl tin dilaurate is 0.2-0.3 parts by weight.
[0012] Preferably, the reaction temperature in (1) is 40-45℃, and the reaction time is 4-5h.
[0013] Preferably, the structure of alkyl isocyanate in (1) is , and a is any integer from 2 to 8.
[0014] Preferably, in (2), the amount of intercalation agent intermediate is 100 parts by weight, and the amount of trimethylamine is 12-17 parts by weight.
[0015] Preferably, the reaction temperature in (2) is 70-80℃, and the reaction time is 12-18h.
[0016] Preferably, the volume ratio of water to ethanol in (3) is 100: (5-10).
[0017] Preferably, the temperature for modification in (3) is 70-85℃, and the modification time is 2-12h.
[0018] Preferably, the amount of bentonite in (3) is 100 parts by weight, and the amount of cationic intercalation agent is 20-50 parts by weight.
[0019] Preferably, the amount of polyurethane in (4) is 100 parts by weight, and the amount of modified bentonite is 2-6 parts by weight.
[0020] Preferably, the temperature of zone 1-5 of the screw extruder in (4) is 150-185℃, and the screw speed is 40-70r / min.
[0021] Preferably, the temperature for film blowing in (4) is 175-185℃.
[0022] Preferably, the TPU closed-cell film is applied to inflatable floating bridges.
[0023] (Three) The beneficial technical effects of the present application: the cationic intercalation agent is used for ion exchange intercalation modification of bentonite, and then is melt blended with polyurethane to blow a film to obtain a TPU closed gas film. The organically modified bentonite is not easy to aggregate, and the dispersibility is good. At the same time, a large number of urethane groups are introduced, which form strong hydrogen bond with the urethane of polyurethane, thereby improving the interfacial bonding force of bentonite and polyurethane, the compatibility of the two is good, the bentonite is uniformly dispersed in the polyurethane film matrix to form a continuous barrier network, which is beneficial to reduce the gas permeability, improve the tensile properties, barrier properties and mechanical properties, and has good practical application in the aspects of inner layer closed gas film in inflatable floating bridge, etc. BRIEF DESCRIPTION OF DRAWINGS
[0024] Figure 1 is the infrared spectrum of the cationic intercalation agent prepared in Example 1. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0026] According to the method of journal literature Inorganica Chimica Acta, 2017, vol. 467, p. 343-350, Cyclen-based chelators for the inhibition of Aβ aggregation: Synthesis, antioxidant and aggregation evaluation, bis(2-hydroxyethyl)acetamide bromide is prepared, and the structural formula is .
[0027] Example 1:
[0028] (1) 10 g of bis(2-hydroxyethyl)acetamide bromide, 9.1 g of n-butyl isocyanate, and 20 mg of dibutyltin dilaurate were added to 200 mL of dichloromethane, heated to 40℃, and stirred and condensed to reflux for 5 h. After filtration, the filtrate was rotary evaporated, and the product was recrystallized in ethanol to obtain an intercalation agent intermediate.
[0029] (2) 20 g of the intercalation agent intermediate and 7.5 mL of an aqueous solution containing 3 g of trimethylamine were added to 250 mL of ethanol, heated to 75℃, and stirred and condensed to reflux for 18 h. After filtration, the filtrate was heated and volatilized, cooled in an ice water bath, and recrystallized to obtain a cationic intercalation agent. Figure 1 The infrared spectrum of the cationic intercalation agent is shown in Figure 1.-1 2865 cm -1 is the stretching vibration peak of -CH3, -CH2-, 1747 cm -1 1651 cm -1 is the stretching vibration peak of C=O in urethane group and amide bond, 1472 cm -1 is the characteristic peak of quaternary ammonium salt C-N + bond.
[0030] (3) 50 g of bentonite was added to 4 L of water, ultrasonic dispersion was performed for 20 min, 10 g of cation intercalation agent, 200 mL of ethanol were added, and the mixture was heated to 80°C and modified by stirring and condensing reflux for 2 h. After filtration, the filter cake was washed with ethanol and dried to obtain modified bentonite.
[0031] (4) 1 kg of polyurethane (Wanhua TPU WHT-1195, same below) and 20 g of modified bentonite were mixed and melt-extruded through a screw extruder, with the temperature of 1-5 zones being 150°C, 170°C, 180°C, 185°C, 185°C, and the screw rotation speed being 40 r / min. Then the material particles were blown into a film through a film blowing machine at a blowing temperature of 175°C to obtain a TPU closed-cell film.
[0032] Example 2:
[0033] (1) 10 g of bis(2-hydroxyethyl)acetamide bromide, 14 g of octyl isocyanate, and 30 mg of dibutyltin dilaurate were added to 300 mL of dichloromethane, and the mixture was heated to 40°C and reacted by stirring and condensing reflux for 5 h. After filtration, the filtrate was rotary evaporated, and the product was recrystallized in ethanol to obtain an intercalation agent intermediate.
[0034] (2) 20 g of the intercalation agent intermediate and 6 mL of an aqueous solution containing 2.4 g of trimethylamine were added to 300 mL of ethanol, and the mixture was heated to 70°C and reacted by stirring and condensing reflux for 18 h. After filtration, the filtrate was heated and evaporated, cooled in an ice water bath, and recrystallized to obtain a cation intercalation agent.
[0035] (3) 50 g of bentonite was added to 4 L of water, ultrasonic dispersion was performed for 30 min, 18 g of cation intercalation agent and 400 mL of ethanol were added, and the mixture was heated to 70°C and modified by stirring and condensing reflux for 12 h. After filtration, the filter cake was washed with ethanol and dried to obtain modified bentonite.
[0036] (4) 1 kg of polyurethane and 40 g of modified bentonite were mixed and melt-extruded through a screw extruder, with the temperature of 1-5 zones being 150°C, 170°C, 180°C, 185°C, 185°C, and the screw rotation speed being 40 r / min. Then the material particles were blown into a film through a film blowing machine at a blowing temperature of 175°C to obtain a TPU closed-cell film.
[0037] Example 3:
[0038] (1) Into 300 mL dichloromethane, add 10 g of bis(2-hydroxyethyl)acetamide bromide, 6.6 g of ethyl isocyanate, 23 mg of dibutyltin dilaurate, heat to 45°C, stir and reflux with condensation for 4 h, filter, and then rotary evaporate the filtrate. Recrystallize the product in ethanol to obtain an intercalation agent intermediate.
[0039] (2) Into 300 mL ethanol, add 20 g of the intercalation agent intermediate, 8.5 mL of an aqueous solution containing 3.4 g of trimethylamine, heat to 80°C, stir and reflux with condensation for 12 h, filter, heat and evaporate the filtrate, cool in an ice water bath, and recrystallize to obtain a cationic intercalation agent.
[0040] (3) Into 4 L of water, add 50 g of bentonite, ultrasonically disperse for 30 min, add 25 g of the cationic intercalation agent, 400 mL of ethanol, heat to 85°C, stir and modify for 8 h with reflux and condensation, filter, wash the filter cake with ethanol, and dry to obtain modified bentonite.
[0041] (4) Mix 1 kg of polyurethane and 60 g of the modified bentonite, melt extrude through a screw extruder, with the temperature of 1-5 zones being 150°C, 170°C, 180°C, 185°C, 185°C, and the screw rotation speed being 70 r / min; then blow the material into a film through a film blowing machine, with the blowing temperature being 185°C, to obtain a TPU closed-cell film.
[0042] Comparative Example 1:
[0043] (1) Mix 1 kg of polyurethane and 20 g of bentonite, melt extrude through a screw extruder, with the temperature of 1-5 zones being 150°C, 170°C, 180°C, 185°C, 185°C, and the screw rotation speed being 40 r / min; then blow the material into a film through a film blowing machine, with the blowing temperature being 175°C, to obtain a TPU closed-cell film.
[0044] Comparative Example 2:
[0045] (1) Into 4 L of toluene, add 50 g of bentonite, ultrasonically disperse for 20 min, add 10 g of the intercalation agent intermediate, heat to 80°C, and stir for 2 h; filter, wash the filter cake with ethanol, and dry to obtain modified bentonite.
[0046] (2) Mix 1 kg of polyurethane and 20 g of the modified bentonite, melt extrude through a screw extruder, with the temperature of 1-5 zones being 150°C, 170°C, 180°C, 185°C, 185°C, and the screw rotation speed being 40 r / min; then blow the material into a film through a film blowing machine, with the blowing temperature being 175°C, to obtain a TPU closed-cell film.
[0047] Comparative Example 3:
[0048] (1) Into 4 L of water, 50 g of bentonite was added and ultrasonically dispersed for 20 min, 10 g of n-hexadecyl trimethyl ammonium bromide and 200 mL of ethanol were added, heated to 80℃, and stirred and condensed to reflux for 2 h of modification. After filtration, the filter cake was washed with ethanol and dried to obtain modified bentonite.
[0049] (2) 1 kg of polyurethane and 20 g of modified bentonite were mixed and melt-extruded through a screw extruder, with the temperature of 1-5 zones being 150℃, 170℃, 180℃, 185℃, 185℃, and the screw rotation speed being 40 r / min; then the material particles were blown into a film through a film blowing machine, with the blowing temperature being 175℃, to obtain a TPU closed gas film.
[0050] Comparative Example 4:
[0051] (1) Into 4 L of toluene, 50 g of bentonite was added and ultrasonically dispersed for 20 min, 10 g of n-butyl isocyanate was added, heated to 80℃, and stirred for 2 h of reaction. After filtration, the filter cake was washed with ethanol and dried to obtain modified bentonite.
[0052] (2) 1 kg of polyurethane and 20 g of modified bentonite were mixed and melt-extruded through a screw extruder, with the temperature of 1-5 zones being 150℃, 170℃, 180℃, 185℃, 185℃, and the screw rotation speed being 40 r / min; then the material particles were blown into a film through a film blowing machine, with the blowing temperature being 175℃, to obtain a TPU closed gas film.
[0053] The gas permeability of the TPU closed gas film was tested according to the GB / T 1038.1-2022 standard, and the test gas was nitrogen.
[0054] The tensile properties were tested according to the GB / T 528-2009 standard.
[0055] The performance test results of the TPU closed gas film are shown in Table 1.
[0056] Table 1 Performance test results of TPU closed gas film
[0057]
[0058] The bentonite of Comparative Example 1 had poor compatibility with polyurethane and was difficult to uniformly disperse in the polyurethane film matrix, resulting in a large gas permeability, poor barrier performance, and low tensile strength and elongation at break, poor mechanical properties.
[0059] The cationic intercalating agent of the embodiments 1-3 contains a quaternary ammonium salt group, can ion exchange intercalation modification to bentonite, the modified bentonite is not easy to gather, and the dispersibility is good, and a large number of urethane groups are introduced, and strong hydrogen bond interaction is formed with the urethane of polyurethane, the interfacial bonding force of bentonite and polyurethane is improved, the compatibility of the two is good, the bentonite is uniformly dispersed in the polyurethane film matrix, a continuous barrier network is formed, which is beneficial to reduce the gas permeability and improve the barrier property, and the tensile strength and elongation at break of polyurethane are increased, and the mechanical property is improved.
[0060] Compared with the embodiment 1, the intercalating agent intermediate of the comparative example 2 does not contain a quaternary ammonium salt group, and cannot ion exchange intercalation modification to bentonite, the gas permeability of the polyurethane material is larger, and the tensile strength and elongation at break are lower.
[0061] The comparative example 3 uses hexadecyl trimethyl ammonium bromide to ion exchange intercalation modification to bentonite, and does not contain a urethane group, the interfacial bonding force of the modified bentonite and polyurethane is weak, the compatibility is low, the gas permeability of the polyurethane material is greater than that of the embodiment 1, and the tensile strength and elongation at break are lower than those of the embodiment 1.
[0062] The comparative example 4 uses the isocyanate group of n-butyl isocyanate to react with the hydroxyl group on the surface of bentonite to obtain modified bentonite, the gas permeability of the polyurethane material is greater than that of the embodiment 1, and the tensile strength and elongation at break are lower than those of the embodiment 1, mainly because the content of the hydroxyl group on the surface of bentonite is less, the grafting reaction effect with n-butyl isocyanate is lower than the ion intercalation modification effect of the quaternary ammonium salt, and the modification effect of bentonite is poor.
[0063] The above is only a preferred specific embodiment of the present application, but the protection scope of the present application is not limited thereto, any person skilled in the art can make equivalent replacement or change according to the technical scheme and the inventive concept of the present application within the technical range disclosed by the present application, which should be covered in the protection scope of the present application.
Claims
1. A TPU air-sealing membrane, characterized in that, The TPU airtight membrane comprises the following components: 100 parts by weight of polyurethane and 2-6 parts by weight of modified bentonite. The modified bentonite is prepared by the following method: adding bentonite to water, ultrasonically dispersing, adding cationic intercalating agent and ethanol, stirring for modification, filtering, washing the filter cake, and drying to obtain modified bentonite; The structural formula of the cationic intercalating agent is as follows: , where a is any integer from 2 to 8; The volume ratio of water to ethanol is 100:(5-10). The amount of bentonite used is 100 parts by weight, and the amount of cationic intercalating agent used is 20-50 parts by weight.
2. The TPU air-sealing membrane according to claim 1, characterized in that, The modification temperature is 70-85℃, and the modification time is 2-12 hours.
3. The TPU air-sealing membrane according to claim 1, characterized in that, The preparation method of the cationic intercalating agent is as follows: (1) Add 100 parts by weight of bis(2-hydroxyethyl)acetamidobromide, 66-140 parts by weight of alkyl isocyanate, and 0.2-0.3 parts by weight of dibutyltin dilaurate to dichloromethane, heat to 40-45℃, stir and reflux for 4-5 hours, filter, recrystallize the product to obtain the intercalating agent intermediate; (2) Add 100 parts by weight of intercalating agent intermediate and 12-17 parts by weight of trimethylamine aqueous solution to ethanol, heat to 70-80℃, stir and reflux for 12-18h, filter, and recrystallize to obtain cationic intercalating agent.
4. The TPU air-sealing membrane according to claim 3, characterized in that, The structural formula of the alkyl isocyanate is as follows: , where a is any integer from 2 to 8.
5. A method for preparing a TPU air-sealing membrane as described in any one of claims 1-4, characterized in that, The preparation method is as follows: polyurethane and modified bentonite are mixed and melt-extruded through a screw extruder, and then the material particles are blown into a film by a blown film machine to obtain a TPU airtight film.
6. The method for preparing the TPU air-sealing membrane according to claim 5, characterized in that, The temperature of zones 1-5 of the screw extruder is 150-185℃, and the screw speed is 40-70 r / min.
7. The method for preparing the TPU air-sealing membrane according to claim 6, characterized in that, The temperature at which the blown film is blown by the blown film machine is 175-185℃.
8. The application of a TPU air-sealing membrane obtained by the preparation method as described in claim 7 in an inflatable floating bridge.
Citation Information
Patent Citations
A polyurethane resin composition for display screen packaging and preparation method thereof
CN117603558B
Block polyurethane polymer, polymer modified bentonite admixture thereof, and preparation and application of block polyurethane polymer and polymer modified bentonite admixture
CN112979905A
Preparation method of degradable barrier film
CN114524958A